Peramalan pendaftar mahasiswa baru dengan menggunakan metode moving average, weighted moving average dan exponential smoothing - Simon, Gusman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Forecasting, which is part of planning activities, provides benefits for higher education institutions to prepare for the needs of the selection process. This study aims to predict the number of new student applicants using the moving average, weighted moving average, and exponential smoothing methods. Forecast accuracy testing through signal tracking tests in each period, as well as MAD, MSE, and MAPE values. The forecast results using the exponential smoothing method with α 0.2 provide the smallest MAD results compared to other methods. The forecast results using the 3-period weighted moving average method with the last weight of 0.8, the second weight of 0.1, and the third weight of 0.1 provide the smallest MSE and MAPE results compared to other methods.